Prenatal features, associated co‐morbidities and clinical course of agenesis of the ductus venosus in the current era. (3rd November 2020) - McBrien, Angela; Caluseriu, Oana; Niederhoffer, Karen Y; Hornberger, Lisa K
Abstract: Objectives: Agenesis of the ductus venosus (ADV) has been associated with additional anomalies in up to 83% of cases. We sought to investigate characteristics, co‐morbidities and outcomes of ADV in the current era. We hypothesized that rates of cardiac and non‐cardiac diagnoses and survival would be higher, due to advances in genetic testing, prenatal diagnosis and surveillance. Methods: A retrospective series of cases diagnosed at our institution from 2007 to 2018 were identified by searching our database. Cardiac and obstetric charts were reviewed for cardiac and extra‐cardiac anomalies, genetic results and outcomes. Results: Fourteen cases were diagnosed at a mean gestational age of 23.9 weeks (range 13‐33). All had associated genetic, cardiac or extra‐cardiac anomalies. Eight (57%) had cardiac anomalies and one other developed cardiomyopathy by 6 months. Extra‐cardiac anomalies were present in 93% (13/14) and genetic diagnoses made in 75% (6/8) of those tested. Cardiac output Z ‐scores were >2 in 60% (6/10) prior to delivery. Two had hydrops, there was one intra‐uterine death, 13 live‐births and two neonatal deaths. Conclusion: Our cohort had more associated diagnoses and a lower mortality than previously reported. In our experience, high output occurs frequently, however with a relatively low risk of hydrops and intrauterine death.